2020
DOI: 10.1177/1687814020907774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the unified strength theory parameters on the failure characteristics and bearing capacity of sand foundation acted by a shallow strip footing

Abstract: The unified strength theory can account for the influence of intermediate principal stress using a specified parameter b, with which the determination of the values and influences of b is significant. In this research, a physical model test was carried out in combination with the numerical simulations to explore the effect of b on a sand foundation loaded by a shallow strip footing. Variation of parameter b would produce significant effect on the deformation characteristics, stress response, failure model, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Extensive true triaxial test results of unsaturated soils [27,28] and predictions of the Drucker-Prager criterion [29] and the unified strength theory [30,31] have confirmed that a conservative result is obtained by utilizing the Mohr-Coulomb criterion without reflecting the influence of intermediate principal stress. Meanwhile, the intermediate principal stress has a marked impact on the strength of saturated soils [32][33][34]. e unified strength theory proposed by Yu [30] is a set of failure criteria including or approximating various conventional ones, and the intermediate principal stress effect can be reasonably reflected.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive true triaxial test results of unsaturated soils [27,28] and predictions of the Drucker-Prager criterion [29] and the unified strength theory [30,31] have confirmed that a conservative result is obtained by utilizing the Mohr-Coulomb criterion without reflecting the influence of intermediate principal stress. Meanwhile, the intermediate principal stress has a marked impact on the strength of saturated soils [32][33][34]. e unified strength theory proposed by Yu [30] is a set of failure criteria including or approximating various conventional ones, and the intermediate principal stress effect can be reasonably reflected.…”
Section: Introductionmentioning
confidence: 99%